Modeling Bacterial Infection Phenomena - B. Kier, Lemont (Current Computer - Aided Drug Design, 2015)
A series of cellular automata models of bacteria were created, where encounters with models of the immune system and a model of an antibiotic drug were present. The dose of the antibiotic, its potency and the timeliness of its administration were variables. The emergence of antibiotic resistance by the bacteria was an outcome associated with the administration of the drug. The models created in these studies were found to closely relate to clinical experiences, making the general model useful for further simulation studies.
Keywords: antibiotics